Ortho-oxygenative 1,2-difunctionalization of diarylalkynes under merged gold/organophotoredox relay catalysis - Sancheti, Shashank P.; Akram, Manjur O.; Roy, Rupam; Bedi, Vaibhav; Kundu, Shubhankar; Patil, Nitin T. (Chemistry-An Asian Journal, 2019)
Reported herein is an ortho-oxygenative 1,2-difunctionalization of diarylalkynes under merged gold/organophotoredox catalysis to access highly functionalized 2-(2-hydroxyaryl)-2-alkoxy-1-arylethan-1-ones. Detailed mechanistic studies suggested a relay process, initiating with gold-catalyzed hydroalkoxylation of alkynes, to generate enol-ether followed by a key formal [4+2]-cycloaddition reaction. The successful application of the present methodology was also shown for the synthesis of benzofurans.
Keywords: binary catalyst system; Gold catalysis; organocatalyst; photoredox; synthetic methodology